INFLUENCE OF PLANT DENSITY, COMPOST AND BIOFERTILIZER ON TRUE SHALLOT SEED GROWTH IN ALLUVIAL SOIL - Gina Aliya Sopha (Indonesian Agency for Agricultural Research and Development, 2020)
True shallot seed (Allium cepa var Aggregatum group) is an alternative way of growing shallot. Different environments and cultivars need a specific study. The aim of this research was to find out the best technology to grow Trisula true shallot seed by managing plant densities and applying compost and biofertilizer in alluvial soils. The study was performed from May to October 2015, using a split-plot design with four replications. The main plot was plant density: 100 plants m-2 and 70 plants m-2. Subplots were five fertilizer application combinations, they were 100% recommended dose of NPK (R-NPK), 100% R-NPK + compost, 100% R-NPK + compost + biofertilizer, 50% R-NPK + compost and 50% R-NPK + compost + biofertilizer. Results showed that biomass and bulb yield were significantly affected by plant density and fertilizer application. The reduced 50% R-NPK by substituting with compost and biofertilizer was unable to maintain shallot bulb yield equal to 100% R-NPK, suggesting insufficient nutrients derived from compost to satisfy the shallot requirement. The best technology to grow true shallot seed of Trisula variety was 100 plants m-2 plant density and 100% NPK (consisting of 180 kg N ha-1, 52 kg P ha-1 and 50 kg K ha-1) with 2.5 t ha-1 compost that achieved the highest bulb yield of 9.83 t ha-1 and increased the revenue.